2022
DOI: 10.1080/02640414.2022.2052428
|View full text |Cite
|
Sign up to set email alerts
|

Relative age effect in French alpine skiing: Problem and solution

Abstract: Objectives: To identify the potential bias of the relative age effect (RAE) in French 16 alpine skiers and to propose a mathematical correction adjustment for such a bias.17Methods: All performances and birthdates of skiers on the national and 18 international circuit were collected from the 2004 up to 2019. A goodness-of-fit 19 chi-square test and the residuals were used to study distribution of birth trimesters 20 in youth competitors. A linear relationship between the distribution of 21 performances and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Relative age gap was defined by the time delay between athlete’s last birthday and competition date, as it can be interpreted as an index to quantify athlete’s experience within his/her age category. Using a method similar previously employed ( De Larochelambert et al, 2022 ; Difernand et al ), linear regressions for each age group between the relative age gap and the average of performances were computed in order to obtain the slope value “ c .” The slope coefficient was converted into days and used to calculate the recalibrated coefficient: r = c*d where “ c” is the slope value and “ d” the number of days until the next birthday. The recalibrated coefficient “ r ” was subtracted (in race events, measured in seconds) or added (in jumps or throws, measured in meters) to the performance in order to obtain rebalanced performances.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative age gap was defined by the time delay between athlete’s last birthday and competition date, as it can be interpreted as an index to quantify athlete’s experience within his/her age category. Using a method similar previously employed ( De Larochelambert et al, 2022 ; Difernand et al ), linear regressions for each age group between the relative age gap and the average of performances were computed in order to obtain the slope value “ c .” The slope coefficient was converted into days and used to calculate the recalibrated coefficient: r = c*d where “ c” is the slope value and “ d” the number of days until the next birthday. The recalibrated coefficient “ r ” was subtracted (in race events, measured in seconds) or added (in jumps or throws, measured in meters) to the performance in order to obtain rebalanced performances.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study ( Brustio et al, 2022 ) applied corrective adjustment procedures (CAPs) as a strategy to remove relative age effects on 689 junior Italian long jumpers. A recent study on French skiers showed that it is possible to cancel out the relative age effect through recalibration ( De Larochelambert et al, 2022 ). Based on a regression coefficient per age category, performances are rebalanced according to their exact age and initial performance ( De Larochelambert et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other study before ( De Larochelambert et al, 2022 ), this study aims to optimize the detection systems of French winter sports. We propose a methodology allowing to estimate the individual progress of the skiers, according to the relation between its performance and their age.…”
Section: Practical Applicationmentioning
confidence: 99%
“…The development of all of one’s abilities does not take place at the same time for all individuals ( Katzmarzyk et al, 1997 ). As a result, selections made at an early age can generate many biases, starting with the relative age effect ( DeCouto et al, 2021 ; De Larochelambert et al, 2022 ; Roaas et al, 2022 ). A retrospective study ( Boccia et al, 2017 ) shows that only 10–25% of elite adult athletes were elite at age 16 in Italian high jump and long jump.…”
Section: Introductionmentioning
confidence: 99%